Global Chronic Total Occlusion Crossing Algorithm - Wu, Eugene B.; Mashayekhi, Kambis; Tsuchikane, Etsuo; Alaswad, Khaldoon; Araya, Mario; Avran, Alexandre; Azzalini, Lorenzo; Babunashvili, Avtandil M.; Bayani, Baktash; Behnes, Michael; Bhindi, Ravinay; Boudou, Nicolas; et al. (Journal of the American College of Cardiology, 2021)
The authors developed a global chronic total occlusion crossing algorithm following 10 steps: 1) dual angiography; 2) careful angiographic review focusing on proximal cap morphology, occlusion segment, distal vessel quality, and collateral circulation; 3) approaching proximal cap ambiguity using intravascular ultrasound, retrograde, and move-the-cap techniques; 4) approaching poor distal vessel quality using the retrograde approach and bifurcation at the distal cap by use of a dual-lumen catheter and intravascular ultrasound; 5) feasibility of retrograde crossing through grafts and septal and epicardial collateral vessels; 6) antegrade wiring strategies; 7) retrograde approach; 8) changing strategy when failing to achieve progress; 9) considering performing an investment procedure if crossing attempts fail; and 10) stopping when reaching high radiation or contrast dose or in case of long procedural time, occurrence of a serious complication, operator and patient fatigue, or lack of expertise or equipment. This algorithm can improve outcomes and expand discussion, research, and collaboration. [Display omitted] •Several regional crossing algorithms for chronic total coronary artery occlusive lesions (CTO) have been published.•The authors of these regional algorithms from 50 countries have collaborated in developing a global CTO crossing algorithm.•This algorithm can encourage discussion, promote research collaboration, facilitate training and improve outcomes of percutaneous revascularization for patients with CTO.